Exploring the impact of eco-anxiety, self- efficacy, environmental knowledge, and social media influence on climate change mitigation behavior among Terengganu youth in malaysian - Mohd Yusof, Nor Khairina Amira; Ma’rof, Aini Azeqa; Muhamad Halmee, Nurul Syahirah; Nashorddin, Nur Afiqah (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the influence of eco-anxiety, self-efficacy, environmental knowledge, and social media influence on climate change mitigation behavior among Terengganu youth, a region highly vulnerable to monsoon flooding and rising sea levels. The findings underscore the importance of equipping youth with environmental knowledge and leveraging social media to foster greater climate action engagement in the region. Using a sample of 428 participants, quantitative methods including correlation and multiple regression analyses were employed to explore the relationships between these variables. The findings revealed that environmental knowledge and social media influence were the strongest predictors of climate change mitigation behavior, followed by self-efficacy and eco-anxiety. These results underscore the importance of equipping youth with environmental knowledge and leveraging social media to foster greater engagement in climate action. Addressing eco-anxiety by channeling it into proactive behaviors and improving self-efficacy are also essential for enhancing youth participation in climate change mitigation efforts. The study provides critical insights into the psychological and social drivers of climate action and offers practical implications for policymakers, educators, and environmental organizations aiming to strengthen youth involvement in climate mitigation strategies in Malaysia.